#### Answer

The graph of the equation is a straight line with points $\left(-3,-7\right),\ \left(-2,-5\right),\left(-1,-3\right),\left(0,-1\right),\left(1,1\right),\left(2,3\right),\left(3,5\right)$ obtained by substituting the given values of $x$ to the equation.

#### Work Step by Step

$$y = 2x - 1$$
If $x=-3$
$y = 2(-3) - 1$
$y = -6 - 1$
$y = -7$
If $x=-2$
$y = 2(-2) - 1$
$y = -4 - 1$
$y = -5$
If $x=-1$
$y = 2(-1) - 1$
$y = -2 - 1$
$y = -3$
If $x=0$
$y = 2(0) - 1$
$y = 0 - 1$
$y = -1$
If $x=1$
$y = 2(1) - 1$
$y = 2- 1$
$y = 1$
If $x=2$
$y = 2(2) - 1$
$y = 4 - 1$
$y = 3$
If $x=3$
$y = 2(3) - 1$
$y = 6 - 1$
$y = 5$
Thus, the graph will have the points $\left(-3,-7\right),\ \left(-2,-5\right),\left(-1,-3\right),\left(0,-1\right),\left(1,1\right),\left(2,3\right),\left(3,5\right)$.